Comparison of Fuzzy Multi-Criteria Methods: Case of Furniture Firms Websites - Yeşilkaya, Murat (Fırat University, 2025)
Multi-Criteria Decision Making (MCDM) methods are successfully applied in different fields and disciplines. However, in many studies, the problem of selecting appropriate methods and parameters for decision problems comes to the fore. In this article, a comparison of MCDM methods is made. AHP, TOPSIS, VIKOR, Fuzzy TOPSIS, and Fuzzy VIKOR were used. To conduct these analyses, the websites of furniture firms were evaluated in relation to the changes that occurred after COVID-19. In application, the literature review and expert opinion determined six main criteria, with a total of 31 criteria. The weights of the criteria used in the AHP method were calculated. Then, the ranking of the websites was obtained according to the results obtained from the methods. Later, the comparison was made based on the factors: the classical ranking of results, rank similarity coefficients, computational complexity, and adequacy to changes of alternatives. The results show that all approaches used are suitable for website evaluation. However, it was observed that the methods produced similar results in the rank similarity coefficients test. VIKOR performed better in computational complexity, and the fuzzy TOPSIS method performed better in compatibility with alternative changes.

Çok Kriterli Karar Verme (ÇKKV) yöntemleri farklı alan ve disiplinlerde başarıyla uygulanmaktadır. Ancak birçok çalışmada karar problemlerine uygun yöntem ve parametrelerin seçilmesi sorunu gündeme gelmektedir. Bu makalede, ÇKKV yöntemlerinin karşılaştırılması yapılmıştır. Yöntemlerden AHP, TOPSIS, VIKOR, Bulanık TOPSIS ve Bulanık VIKOR kullanılmıştır. Bu analizleri yapmak için COVID-19 sonrası değişimlerle mobilya işletmelerinin web siteleri değerlendirilmiştir. Uygulamada literatür taraması ve uzman görüşü sonucunda altı ana kriter olmak üzere toplam 31 kriter belirlenmiştir. AHP yönteminden kullanılan kriterlerin ağırlıklarını hesaplanmıştır. Daha sonra yöntemlerden elde edilen sonuçlara göre web sitelerinin sıralamasını elde edilmiştir. Sonra ise yöntemler klasik sonuçların sıralaması, ilişki testi, işlem karmaşıklığı ve alternatif sayısındaki değişiklik ile karşılaştırılmıştır. Sonuçlar, kullanılan tüm yaklaşımların web sitesi değerlendirmesinde uygun olduğunu göstermektedir. Fakat ilişki testinde yöntemlerin benzer sonuçlar çıktığı, hesaplama karmaşıklığında VIKOR daha iyi performans gösterdiği ve alternatif değişikliklerine uygunlukta ise bulanık TOPSIS yöntemi daha iyi performans gösterdiği gözlemlenmiştir.
Bulanık Çok Kriterli Yöntemlerin Karşılaştırılması: Mobilya İşletmelerinin Web Siteleri Örneği
Keywords: Multiple Criteria Decision Making; Çok Ölçütlü Karar Verme; Industrial Engineering; Endüstri Mühendisliği